Prevención y control de la contaminación causada por buques en el mar territorial: competencias del Estado ribereño y contribución de las organizaciones internacionales (Revista Española de Derecho Internacional, 2008)
The coastal State may adopt the territorial sea in a series of measures to preserve the marine environment that allows it to act pre–emptively before the risks of pollution from ships navigating off its coast. However, also in this space maritime is noted the tension between the protection of the marine environment and freedom of navigation recognized all foreign ships through the right of innocent passage. Thus, some state practice –for the time being not significant– intended to rid the coastal State of the restrictions imposed by UNCLOS, especially in the regulation of the right of innocent passage, to prevent the navigation of any ship potentially dangerous before that the pollutant discharge has occurred. Despite this practice, the prevention of vessel–source pollution must be the result of concerted action by all States, especially through international organisations such as the IMO or the EU, which they are playing a very important role in this area. Only through international cooperation will be achieving this goal in an effective way.